The Warburg Effect Occurs Rapidly in Stimulated Human Adult but Not Umbilical Cord Blood Derived Macrophages - Ó Maoldomhnaigh, Cilian; Cox, Donal J.; Phelan, James J.; Malone, Fergal D.; Keane, Joseph; Basdeo, Sharee A. (Frontiers in Immunology, 2021)
The Warburg effect, defined as increased glycolysis and decreased oxidative phosphorylation, occurs in murine macrophages following LPS stimulation and is required for activation. There are differences between human and murine macrophage metabolic responses to stimulation, with peak metabolite concentrations occurring earlier in humans than mice. Complex changes occur in the human immune system with age, resulting in the very young and the very old being more susceptible to infections. Anti-bacterial immune responses in umbilical cord immune cells are considered deficient but there is a paucity of data on the role that metabolism plays. We hypothesised that metabolic responses in human macrophages occur early during activation. In addition, we hypothesised that umbilical cord derived macrophages have an altered immunometabolic response compared with adult macrophages. We demonstrate that adult and cord blood monocyte derived macrophages (MDM) immediately increase glycolysis in response to stimulation with LPS or Mycobacterium tuberculosis (Mtb), however only adult MDM decrease oxidative phosphorylation. At 24 hours post stimulation, glycolysis remains elevated in both adult and cord blood MDM, oxidative phosphorylation remains unchanged in the cord blood MDM and has normalised in the adult MDM stimulated with Mtb. However, LPS stimulated adult MDM have increased oxidative phosphorylation at 24 hours, illustrating differences in metabolic responses to different stimuli, time-dependent variation in responses and differences in macrophage metabolism in adults compared with umbilical cord blood. We compared the phenotype and function of macrophages derived from adult or cord blood. Cord blood MDM secreted less TNF following Mtb stimulation and more IL-6 following LPS stimulation compared with adult MDM. Our findings demonstrate that whilst cord blood MDM exhibit an immediate increase in glycolytic flux in response to stimulation, similar to adult MDM, cord blood MDM do not concomitantly decrease oxygen consumption. This indicates that adult macrophages shift to Warburg metabolism immediately after stimulation, but cord blood macrophages do not. Understanding the differences in the metabolic profiles of macrophages over a human lifetime will enable the translation of immunometabolism into effective immuno-supportive therapies that could potentially be targeted at vulnerable populations, such as the very old and the very young.